EFEK MODERASI SIFAT MACHIAVELLIAN PADA PENGARUH TIME BUDGET PRESSURE DAN KOMPLEKSITAS TUGAS TERHADAP PERILAKU DISFUNGSIONAL AUDITOR - I Gusti Ayu Eka Wulandari; Putu Irma Yunita; Putu Purnama Dewi (Faculty of Economics and Business, Universitas Warmadewa, 2026)
This research examines how time constraints and task difficulty affect counterproductive audit practices, considering the moderating effect of manipulative personality characteristics. The study utilized survey data from 105 professionals working in public accounting firms throughout Denpasar. Analytical methods included multivariate regression and interaction effect testing. The outcomes demonstrate that both time pressure and task intricacy substantially increase non-compliant audit behaviors. Additionally, Machiavellian disposition significantly intensifies these relationships. These results highlight how personal temperament variables can amplify the effect of workplace stressors on professional conduct deviations within auditing contexts.